Fostering strategic function of public relations corporate - communication in corporate culture practices - Koswara, Aang; Nugraha, Aat Ruchiat; Damayanti, Trie (PRofesi Humas, 2023)
Background: Public relations and Culture are intertwined. Societal and corporate Culture influences public relations practices. Conversely, the existence of public relations influences organizational cultural practices and societal Culture. Regrettably, the human resource department has a more dominant role in corporate culture practices than the public relations department. It is mainly related to internalizing organizational values, while the public relations department supports the internalization program through internal corporate communication channels. Purpose: This paper examines public relations function in corporate culture practices based on stories and opinions from Indonesian communication practitioners. It focuses on three main research questions, first how and what the impacts of the existence of public relations – corporate communication to the development of corporate Culture; Second, what the functions of public relations are – corporate communication to support the building and changing corporate Culture; and third what factors influence the strategic function of public relations - corporate communication in corporate culture practice. Methods: This study employs qualitative methods through semi-structured interviews with public relations/corporate communication professionals working at different corporations and organizations. Results: Based on thematic analysis, the empirical findings revealed that cascading organizational values is still part of the human resource department’s primary job, while corporate communication is essential to echoing the key message. Determining the appropriate communication channels and corporate language is critical to ease misunderstandings amongst corporate members. Finally, the digital business environment frequently invites hostile situations, and therefore strong leadership and agile organization can preserve business sustainability. Conclusion: The influence of public relations is essential to orchestrate various internal communication channels. The agile organization provides ease of organizational bureaucracy in corporate culture practices. Implications: This initial finding contributes to the field of public relations – corporate communication to provide a balanced perspective from Indonesian practitioners.